2022
DOI: 10.1016/j.molcel.2021.11.023
|View full text |Cite
|
Sign up to set email alerts
|

Distal and proximal cis-regulatory elements sense X chromosome dosage and developmental state at the Xist locus

Abstract: Developmental genes such as Xist, which initiates X chromosome inactivation, are controlled by complex cisregulatory landscapes, which decode multiple signals to establish specific spatiotemporal expression patterns. Xist integrates information on X chromosome dosage and developmental stage to trigger X inactivation in the epiblast specifically in female embryos. Through a pooled CRISPR screen in differentiating mouse embryonic stem cells, we identify functional enhancer elements of Xist at the onset of random… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
58
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(71 citation statements)
references
References 172 publications
(207 reference statements)
2
58
0
Order By: Relevance
“…Among the positive regulators of Xist within the same TAD as the Xist promoter, three lncRNA loci have been reported to influence Xist expression in cis and could therefore affect choice-Ftx and Xert via their transcription [62,104], and Jpx transcriptionally or posttranscriptionally [63,105]. Jpx has also been reported as a trans-acting regulator of Xist via its lncRNA [106].…”
Section: Influencing Choice By Influencing Xist Upregulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the positive regulators of Xist within the same TAD as the Xist promoter, three lncRNA loci have been reported to influence Xist expression in cis and could therefore affect choice-Ftx and Xert via their transcription [62,104], and Jpx transcriptionally or posttranscriptionally [63,105]. Jpx has also been reported as a trans-acting regulator of Xist via its lncRNA [106].…”
Section: Influencing Choice By Influencing Xist Upregulationmentioning
confidence: 99%
“…Jpx has also been reported as a trans-acting regulator of Xist via its lncRNA [106]. A recent study has identified a series of proximal and distal enhancers that are also required for activation of Xist upregulation in cis [104]. Elements within the Xist locus itself have also been reported to contribute to Xist upregulation-e.g., [107], including an antisense transcript, XistAR [108].…”
Section: Influencing Choice By Influencing Xist Upregulationmentioning
confidence: 99%
“…Xist expression is controlled by a large genomic region, which contains a series of lncRNA loci, thought to repress (Tsix, Linx) or activate (Jpx, Ftx, Xert) Xist transcription mostly in cis (15,16). Large (210-460 kb) single-copy Xist-containing transgenes (tg53, tg80), encompassing ~100kb genomic sequence upstream of Xist, can recapitulate initial Xist upregulation after fertilization and maintenance in extraembryonic lineages, but not rXCI in somatic tissues (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with Jpx escaping XCI, female mouse ES cells express twice the expression level as males ( Sun et al, 2013 ), but whether that means that autosomal Jpx developmental gene targets are expressed at a higher level in female versus male preimplantation embryos was not determined in this study. Another recently described activator of Xist in XX mouse ES cells is an enhancer localized lncRNA called Xert ( Gjaltema et al, 2021 ). Unlike Jpx , whose expression is ubiquitous in somatic tissues, the expression of Xert appears limited to the mouse epiblast at embryonic days 5.5–6.5 ( Gjaltema et al, 2021 ), but expected sex differences in embryonic Xert expression were not directly determined in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Another recently described activator of Xist in XX mouse ES cells is an enhancer localized lncRNA called Xert ( Gjaltema et al, 2021 ). Unlike Jpx , whose expression is ubiquitous in somatic tissues, the expression of Xert appears limited to the mouse epiblast at embryonic days 5.5–6.5 ( Gjaltema et al, 2021 ), but expected sex differences in embryonic Xert expression were not directly determined in this study.…”
Section: Introductionmentioning
confidence: 99%